Subject–verb agreement and verbal short-term memory: A perspective from Greek children with specific language impairment. Issue 3 (June 2016) - Lalioti, Marina; Stavrakaki, Stavroula; Manouilidou, Christina; Talli, Ioanna
This study investigated the performance of school age Greek-speaking children with SLI on verbal short-term memory (VSTM) and Subject–Verb (S-V) agreement in comparison to chronological age controls and younger typically developing children. VSTM abilities were assessed by means of a non-word repetition task (NRT) and an elicited production task, an off-line grammaticality judgment (GJ) task, and an on-line self-paced listening task were employed to examine S-V agreement abilities. The study found significant between-group differences in the NRT and the off-line GJ task. No significant between-group differences were found for the S-V agreement production task and for reaction times of the on-line task. The authors argue that the children with SLI showed increased grammatical sensitivity in S-V agreement and relate their lower performance on the off-line GJ task to the task's metalinguistic demands. The findings suggest that deficits in VSTM constitute a robust marker for SLI and claim that S-V agreement can be acquired by SLI individuals with apparent limitations in VSTM.